PEMBELAJARAN BERBASIS SIMULASI MENINGKATKAN PENGETAHUAN FIRST-AID PADA KONDISI GAWAT DARURAT MAHASISWA KEPERAWATAN: PRE-POST PRE-EXPERIMENTAL STUDY - Suwarno; Bambang Sudono Dwi Saputro; Emy Kurniawati; Resi Putri Naulia; Esri Rusminingsih (Jurnal Cakrawala Keperawatan, 2026)
Background: First Aid in emergency situations is an essential skill that nursing students must possess. Adequate knowledge of First Aid is crucial in saving lives and preventing the worsening of patients’ conditions. However, many students still have suboptimal levels of First Aid knowledge. Objective: This study aims to analyze the effect of simulation-based learning on First Aid knowledge in emergency situations among nursing students at STIKES Estu Utomo. Method: This research used a one-group pretest-posttest design without a control group. A total of 43 nursing students were selected using a total sampling technique. Data were collected using a questionnaire and analyzed using paired t-test. Results: Before the intervention, the average knowledge score was 62.74 ± 9.446. After simulation-based learning, the average score increased to 77.29 ± 7.717, with a mean difference of 14.559 ± 1.408. The paired t-test showed a significant difference with a p-value of 0.001 (p < 0.05), and the 95% confidence interval ranged from 11.694 to 17.423. Conclusion: Simulation-based learning is proven effective in increasing nursing students’ knowledge of First Aid in emergency situations. It is recommended that this method be implemented in nursing education curricula to enhance students’ readiness in responding to emergencies professionally